A Study of K- Factor Power Transformer Characteristics by Modeling Simulation - Gouda, O. E.; Amer, G. M.; Salem, W. A. A. (Engineering, Technology & Applied Science Research, 2011)
Harmonic currents generated by nonlinear loads can cause overheating and premature failure in power transformers. K-factor transformers are specially designed to accommodate harmonic currents and offer protection against overheating caused by harmonics. They minimize harmonic current loss and have an additional thermal capacity of known limits. According to IEEE C57-110, the winding eddy current losses are considered proportional to the harmonic current squared times its harmonic number. K-factor is only an indicative value and the authors' main objective in this paper is to study the effect of harmonics on oil filled transformer and to simulate harmonic behavior using Matlab Simulink. A case study is simulated in order to investigate K-factor values with pumping loads, with and without the use of harmonic filters. Results are compared with measured values.